Effect of endogenous methane production: a step forward in the validation of biochemical methane potential (BMP) tests - Oliveira, João Vítor (2022)
This work evaluates the influence of the inoculum type, the pre-consumption of the residual substrate and the ratio of blanks’ headspace volume to working volume (Hv Wv−1, 0.6 to 10) on Biochemical Methane Potential (BMP) measurements when methane is monitored by gas chromatography. Different inocula were tested: digested sewage sludge—DSS, granular sludge—GS and fresh dairy manure—DM. Microcrystalline cellulose was used as the substrate. BMP surpassed the maximum theoretical value (BMPmax=414 L kg−1) when methane produced in the blanks was not discounted, showing that degassing cannot stand alone as an alternative to the procedure of discounting the inoculum’s background production. Still, when the residual substrate concentration is high (e.g., in DM), degassing is mandatory because methane produced from its digestion will conceal the methane produced from the substrate in the BMP determination. For inocula with a low residual substrate (e.g., GS), short degassing periods are recommended in order to avoid detrimental effects on methanogenic activity. For moderate residual substrate concentrations (e.g., DSS), BMP values closer to BMPmax (90–97%) were achieved after degassing and discounting the blanks with lower Hv Wv−1. For higher Hv ∙ Wv−1, less accurate quantification occurred, likely due to error propagation. Proper inoculum pre-incubation time and discounting the methane production from blanks with low Hv Wv−1 (adjusted according to the estimated background methane) are essential for accurate BMP determinations.